Effects of the ageing treatment on the superelastic behavior of a nitinol stent for an application in the esophageal duct - Nematzadeh, Fardin (Materiali in tehnologije, 2013)
The effects of design parameters and material properties obtained with the ageing treatment on the mechanical performance of a z-shaped esophageal-duct nitinol wire stent under the crushing tests for clinical applications are investigated with a finite-element simulation. With 90 % crushing, low chronic outward force, high radial resistive strength and favorable superelastic behavior are attained at the segment angle of 65° and the Af temperature of 24 °C. The performance of the stent is seen to drastically vary with a change of only 1° in the segment angle.
Keywords: protetika; požiralnik; materiali; elastičnost; opornice; staranje materialov; analiza končnih elementov